Influence of chemical additives for warm mix asphalts on the short-term ageing of a plain bitumen. (30th April 2019) - Ragni, Davide; Ferrotti, Gilda; Lu, Xiaohu; Canestrari, Francesco
Abstract : Over the last years, the use of warm mix asphalt (WMA) in asphalt industry allows important reductions in production and compaction temperatures guarantying relevant environmental benefits. However, the most proper laboratory procedure for short-term ageing of WMAs must still be defined. This study aims at evaluating the effect of temperature and chemical additives on bitumen short-term ageing. For this purpose, a 70/100 pen-grade bitumen and two chemical additives were investigated in terms of conventional (penetration, softening point), viscosity and rheological tests, as well as FTIR-ATR analysis. As expected, binders aged at lower temperatures show reduced oxidation as compared to those aged at higher temperatures, implying a lower oxidative hardening. In general, aged binders containing the chemical additives show a reduction of the effect of ageing, or anti-ageing effect. Moreover, the rheological model parameters of the binders present good correlations with penetration values and softening point temperatures, as well as with the chemical parameters determined by FTIR-ATR.